Pain threshold in the masticatory and cervical muscles in different types of temporomandibular disorders - Oliveira, Nattalia de; Marques, Ana Elisa Zulliani Stroppa; Pucci, Renata Lumena Altruda; Sousa, Érica Almeida; Ribeiro, Flora Tolentino; Navega, Flavia Roberta Faganello; Pedroni, Cristiane Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Given the intimate connection of the temporomandibular joint in the cervical region and its functions of chewing, speech and swallowing, patients with temporomandibular disorders (TMD) have most painful condition in stomathognatic muscles. Objective: Check for differences in pressure pain threshold of the masseter (MS), temporalis (TM), upper trapezius (UT) and sternocleidomastoid (SCM) muscles in different types of TMD. Method: Participated in the research 97 subjects, classified according to “The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD)”: myofascial pain (TMD IA), myofascial pain with limited opening (TMD IB), disc displacement with reduction (TMD IIA), disc displacement without reduction and with limited opening (TMD IIB), disc displacement without reduction and without limited opening (TMD IIC). For measurement of the pressure pain threshold (PPT) was used the pressure algometry program (Kratos) of the TM, MS, UT and SCM muscles. For statistical analysis was used the Graphpad Instat program with the Kruskal-Wallis test. Results: The sample consisted of 67 women and 30 men with an average age of 22.09 ± 5.45 years. Of these subjects, 40 were classified as “with TMD”, 57 as “without TMD”, 34 as “TMD IA”, 16 as “TMD IB”, 14 as “TMD IIA” and nobody as “TMD IIB” and “TMD IIC”. The MS, TM and UT muscles showed decreased threshold in myogenic groups of TMD with relation to the group without TMD. Only the masseter muscle showed statistical significance when compared to the myogenic groups with each other, demonstrating that the IB group has lower PPT. Individuals with TMD IB showed lower PPT of MS, TM and UT muscles when compared to TMD IIA. Conclusion: There is a significant difference comparing the PTT of MS, TM and UT muscles of myofascial pain subgroup to the subgroup without TMD. There were differences between the groups myogenic in PPT of MS. TMD IB showed lower threshold in TMD IB group than in TMD IIA group. Controversially, it was not observed when comparing the SCM muscle and disc displacement subgroup with the subgroup without TMD.